Pemanfaatan Dan Penyuluhan Serai Menjadi Semprotan Anti Nyamuk Kepada Masyarakat - Huda, Hairul; Fathoni, Rif’an; Diwa Larasati, Tantra (ReTII, 2022)
Mosquitoes are insects that carry many diseases to humans, such as Dengue Hemorrhagic Fever (DHF) and Malaria. This disease is prone to outbreaks in tropical or subtropical regions, especially during the rainy season. In puddles, mosquitoes can lay eggs and breed, causing a mosquito population explosion. This is very dangerous, mainly if it occurs in a community residential area. Therefore, efforts are needed to prevent the development of mosquito breeding, in addition to maintaining a clean environment and ensuring that there is no stagnant water. Steps are required to protect yourself from mosquito attacks, which can be done by using repellents or mosquito repellents. The materials used must also be natural and not use hazardous chemicals that can damage the environment or cause health problems. One is using the lemongrass plant, which contains citronellol and geraniol. This activity aims to provide information on the manufacture of mosquito repellent spray from lemongrass for the community. Anti-mosquito sprays do not harm the skin or health and are easy to make for the public.